Bài 2.
a.\(\dfrac{1}{8}-\dfrac{3}{8}x=-\dfrac{7}{12}\)
\(-\dfrac{3}{8}x=-\dfrac{17}{24}\)
\(x=-\dfrac{17}{24}:-\dfrac{3}{8}\)
\(x=\dfrac{17}{9}\)
b.\(-\dfrac{12}{7}-\left(x+\dfrac{1}{4}\right)^2=-\dfrac{75}{7}\)
\(-\left(x+\dfrac{1}{4}\right)^2=-9\)
\(\left(x+\dfrac{1}{4}\right)^2=9\)
\(\rightarrow\left[{}\begin{matrix}x+\dfrac{1}{4}=3\\x+\dfrac{1}{4}=-3\end{matrix}\right.\) \(\rightarrow\left[{}\begin{matrix}x=\dfrac{11}{4}\\x=\dfrac{13}{4}\end{matrix}\right.\)
B1
a) \(\dfrac{3}{8}-\dfrac{5}{8}\cdot\left(\dfrac{-3}{2}\right)^2=\dfrac{3}{8}-\dfrac{5}{8}\cdot\dfrac{9}{4}=\dfrac{3}{8}-\dfrac{45}{32}=\dfrac{12}{32}-\dfrac{45}{32}=-\dfrac{33}{32}\)
b) \(\dfrac{-7}{16}\cdot\dfrac{1}{2}\cdot\dfrac{16}{7}\cdot\dfrac{-2}{15}=-\dfrac{7}{32}\cdot\left(-\dfrac{32}{105}\right)=\dfrac{1}{15}\)
B2
a) \(\dfrac{1}{8}-\dfrac{3}{8}x=\dfrac{-7}{12}\)
\(\dfrac{3}{8}x=\dfrac{1}{8}-\left(\dfrac{-7}{12}\right)\)
\(\dfrac{3}{8}x=\dfrac{17}{24}\)
\(x=\dfrac{17}{24}:\dfrac{3}{8}\)
\(x=\dfrac{17}{9}\)
b) \(\dfrac{-12}{7}-\left(x+\dfrac{1}{4}\right)^{^2}=\dfrac{-75}{7}\)
\(\dfrac{-12}{7}-\left(x+\dfrac{1}{16}\right)=\dfrac{-75}{7}\)
\(x+\dfrac{1}{16}=\dfrac{-12}{7}-\dfrac{-75}{7}\)
\(x+\dfrac{1}{16}=9\)
\(x=9:\dfrac{1}{16}\)
\(x=144\)
Bài 1:
a,=3/8-5/8.9/4
=-33/32
b,-7/16.1/2.16/7.-2/15=1/15
\(2,\)
\(a,\dfrac{1}{8}-\dfrac{3}{8}x=-\dfrac{7}{12}\)
\(\Leftrightarrow\dfrac{3}{8}x=\dfrac{1}{8}+\dfrac{7}{12}\)
\(\Leftrightarrow\dfrac{3}{8}x=\dfrac{17}{24}\)
\(\Leftrightarrow x=\dfrac{17}{24}:\dfrac{3}{8}\)
\(\Leftrightarrow x=\dfrac{17}{24}\times\dfrac{8}{3}\)
\(\Leftrightarrow x=\dfrac{136}{72}\)
\(\Leftrightarrow x=\dfrac{17}{9}\)
\(b,-\dfrac{12}{7}-\left(x+\dfrac{1}{4}\right)^2=-\dfrac{75}{7}\)
\(\Leftrightarrow\left(x+\dfrac{1}{4}\right)^2=-\dfrac{12}{7}+\dfrac{75}{7}\)
\(\Leftrightarrow\left(x+\dfrac{1}{4}\right)^2=9\)
\(\Leftrightarrow x+\dfrac{1}{4}=\sqrt{9}\)
\(\Leftrightarrow x+\dfrac{1}{4}=3\)
\(\Leftrightarrow x=3-\dfrac{1}{4}\)
\(\Leftrightarrow x=\dfrac{12}{4}-\dfrac{1}{4}\)
\(\Leftrightarrow x=\dfrac{11}{4}\)
Bài 1.
a.\(\dfrac{3}{8}-\dfrac{5}{8}.\left(-\dfrac{3}{2}\right)^2\)
\(=\dfrac{3}{8}-\dfrac{5}{8}.\dfrac{9}{4}\)
\(=\dfrac{3}{8}-\dfrac{45}{32}\)
\(=-\dfrac{33}{32}\)
b.\(-\dfrac{7}{16}.\dfrac{1}{2}.\dfrac{16}{7}.\dfrac{-2}{15}\)
\(=\dfrac{-7.16}{16.7}.\dfrac{1.-2}{2.15}\)
\(=-1.-\dfrac{1}{15}=\dfrac{1}{15}\)